2012
DOI: 10.1042/cbi20110504
|View full text |Cite
|
Sign up to set email alerts
|

Melamine causes apoptosis of rat kidney epithelial cell line (NRK‐52e cells) via excessive intracellular ROS (reactive oxygen species) and the activation of p38 MAPK pathway

Abstract: There was an outbreak of urinary stones associated with consumption of melamine-tainted milk products in 2008 in China, leading to serious illness of many infants and even death. We have recently demonstrated that melamine causes oxidative damage on the NRK (normal rat kidney)-52e cells. The objective of this study was to explore the cellular signalling pathway that mediates the cell apoptosis induced by melamine in the NRK-52e cells. Fluorescence microscope showed that melamine enhanced intracellular ROS (rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 31 publications
(36 reference statements)
2
23
0
Order By: Relevance
“…Several previous studies showed that melamine could induce oxidative damage by enhancing ROS level and promoting depletion of antioxidant [49,50]. Moreover, one of previous investigations reported that melamine induced PC12 cells death by enhancing intracellular ROS level [12].…”
Section: Discussionmentioning
confidence: 97%
“…Several previous studies showed that melamine could induce oxidative damage by enhancing ROS level and promoting depletion of antioxidant [49,50]. Moreover, one of previous investigations reported that melamine induced PC12 cells death by enhancing intracellular ROS level [12].…”
Section: Discussionmentioning
confidence: 97%
“…Previous results showed that the phosphorylation of P38 was involved in the course of macrophagemediated inflammation induced by AGEs in DN (Qin et al, 2012), the ERK1/2 and p38 MAPK pathways participated in the TGF-β independent Smad3 pathway to promote the development of DN (Chung et al, 2010), the inhibition of p38 MAPK pathway blocked the apoptosis of proximal tubules by suppressing excessive intracellular ROS (Guo et al, 2012), and the inhibition of MAPK pathway reduced ECM production in mesangial cells and prevented DN in mice (Taniguchi et al, 2013). The results of our study suggested that MAPK pathway was markedly activated in response to GA stimulation, and pretreatment with antioxidants such as NAC, Apo or Nox4 siRNA transfection could reduce the activation of MAPK pathway based on the detection of pP38, pERK1/2 and pJNK analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Several kinds of tableware are also made of melamine, which can migrate into food when that tableware comes into contact with high temperatures or acid . Several research groups studying long‐term low‐dose melamine exposure have suggested that melamine‐induced oxidative stress and inflammation play pathological roles in renal injury . Epidemiological studies have also associated melamine exposure and early renal injury markers in children and occupational workers …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Several research groups studying long-term low-dose melamine exposure have suggested that melamine-induced oxidative stress and inflammation play pathological roles in renal injury. [12][13][14][15][16] Epidemiological studies have also associated melamine exposure and early renal injury markers in children and occupational workers. 6,17,18 One review study has reported an increase in the number of animal studies suggesting that melamine may have physiological impacts beyond renal dysfunction, affecting reproductive function, neurology and anthropometric outcomes.…”
Section: Introductionmentioning
confidence: 99%